Análise citogenética em espécies do gênero Hypostomus Lacépède, 1803 (siluriformes: loricariidae) de afluentes da bacia do alto rio Paraná - PR, Brasil : uma contribuição a diversidade cariotípica do gênero - Lara-Kamei, Marcia Cristina de Souza (2015)
The genus Hypostomus Lacépède, 1803, is composed of small fishes to large popularly known as catfishes. Due to the hight morphological similarities among the species of Hypostomus, there is difficulty in the taxonomic status of the definition of these, the cytogenetic analysis have contributed significantly as a cytotaxonomic tool to the group. Hypostomus is characterized by a wide variation in the diploid number (54-84 chromosomes) having different karyotype formulas, indicating divergent evolution for this group. Therefore, this study aimed to analyze cytogenetically different species of Hypostomus collected in two tributaries of upper Paraná river basin to obtain species-specifics possible characters, contributing this way to the taxonomy of this group, as well as adding data to inferences about their karyotype evolution. In Keller river (tributary of Ivai river basin) were analyzed - H .ancistroides, Hypostomus cf. topavae, and Hypostomus aff hermanni. In addition to these species, three populations of Hypostomus paulinus were collected in Mourão and Keller rivers (tributary of Ivai river) and Atlantic stream (tributary of Pirapo river). The species were submitted to conventional analysis as Giemsa coloration, impregnation by silver nitrate, C-banding and molecular cytogenetically technique of Double FISH with rDNA 18S and 5S probes. H. ancistroides observed 2n = 68 chromosomes with 16m+12sm+22st+18a, FN=118 for males and 16m+13sm+22st+17a, with FN = 119 for females, featuring a chromosome system of sex determination of the type ZZ / ZW. This species presented a multiple NORs (three chromosome pairs) system detected by silver nitrate (Ag-NORs) and rDNA 18S probe. The heterochromatin was found in pericentromeric region of most chromosomes, in NORs regions and bitelomerics blocks on short arms of pair 14, and telomeric on long arm of pair 31, not marked in sexual pairs. FISH with rDNA 18S probe revealed multiple sites (2 chromosome pairs) located in interstitial and telomeric position. Hypostomus cf. topavae showed 2n=80 chromosomes being 14m+30sm+18st+1a in both genders. This specie showed multiple NORs (3 chromosome pair) detected by silver nitrate and rDNA 18S. The heterochromatin was found in pericentrometrics region of many chromosomes, in NORs regions and in telomerics blocks on short arm of pairs 7 and 15 and telomerics blocks of long arm of pair 18. FISH with rDNA 5S probe showed multiple sites (2 chromosomes pairs) located in interstitial and telomerics positions. For Hypostomus aff. hermanni was found a diploid number of 2n=72, with 12m+22sm+18st+20a and FN=124 without chromosome differentiation between the genders. One multiple NOR system (Ag-NORs and FISH 18S) involving three pairs of chromosome was found too. The heterochromatin was observed in pericentromeric region of most chromosomes, in pairs Ag-NORs, in telomerics blocks of short arm of pairs 1 and 4, large blocks telomeric marking the long arm of pair 23. FISH with rDNA 5S showed an interstitial marking in just a pair of metacentric chromosomes. High diploid numbers, multiple NORs and extensive blocks of heterochromatin in some chromosomes reaffirm the hypothesis of derived karyotypes within Locariidae. Furthermore, the karyotype formulas described for H. ancistroides, Hypostomus cf. topavae and Hypostomus aff. hemanni, differ from other populations found in literature, especially the unprecedented fact of a sexual chromosome system ZZ\ZW for H. ancistroides. The individuals of H. paulinus of three analyzed populations showed diploid number of 76 chromosomes, with the karyotype formula of 10m+14sm+24ST+28a, FN=124 and without chromosome differentiation between the genders. However, the karyotypes of the populations differ in the number of nucleolar chromosomes (Ag-NORs) localizations of rDNA 5S sites and distribution of constitutive heterochromatin. The populations of Keller and Mourão rivers showed the three pairs of nucleolar chromosomes, 9, 20 and 28 while Atlantic stream population showed just one pair of chromosomes (pair 9) whose markings by silver impregnation were confirmed by FISH 18S. The distribution of constitutive heterochromatin was evidenciated in pericentrometrics and telomerics regions in most of chromosomes of Keller river population and fewer in of Mourão river and Atlantic stream and coincides with the Ag-NORs pairs in the three populations. However each population detached by the presence of large heterochromatic blocks. In the Keller river population standed out pairs 1, 12, 16, 23 with markings all along the short arm, the long arm of pair 25 (biggest acrocentric) and a bitelomeric marking the pair 22 heteromarking short arm; and the pair and 35 with telomerics blocks on long arm. In the population of Mourão river stands out a large interstitial block of long arm of pair 29 and in the Atlantic stream population stands out heterochromatic blocks on short arm of pair 5, an interstitial block in the long arm of pair 16 and telomeric blocks in the long arm of pairs 20 and 22. Regarding the number and distribution of 5S rDNA sites there were also variation between populations, however, the three populations had in common a pair of metacentric carriers of interstitial 5S sites. Whereas the population of the Atlantic stream there was only the pair of metacentric carrier 5S site, additional sites were located on the short arms of two submetacentrics pairs and two subtelocentric pairs in populations of Keller and Mourão rivers. Therefore chromosome data obtained for the three populations of H. paulinus featuring a polymorphism of heterochromatin and NORs, allowing differentiation in karyotype microstructure suggesting new evolutionary trends for this species. In summary, the data obtained in the present corroborate the karyotype diversity in the Hypostomus genus, contributing significantly with information supporting the hypothesis that H. ancistroides is a species complex and that the three populations of H. paulinus are suffering a process of karyotype evolution involving dispersion of heterochromatin and nucleolar organizing regions.